1956
DOI: 10.1161/01.res.4.4.440
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Fibrinolytic Activity and Pharmacology of Various Plasmin (Fibrinolysin) Preparations

Abstract: A quantitative method based on the disappearance of I 111 laljeled fibrin h;is been used to study the in vivo effect of fibrinolytic agents. Various preparations of human and bovine plasmin were found to lyse clots effectively. The minimal effective dose of human plasmin prepared by the method of Kline was 15 Loomis units/Kg. Plasmin preparations given intravenously produced hypotension and leukopeniii followed by leukocytosis. Doses above 30 Loomis units/Kg, caused decrease in fibrinogen level and clotting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1958
1958
1966
1966

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Control clots of the same age showed little decrease of radioactivity levels. A Resistance to lysis is apparent from the observation that most of the fibrinolytic effect is obtained within 24 hours after the first injection of plasmin, the remaining portions of the clot exhibiting less and less lysis during the subsequent days of treatment (2). It was found that the ability of plasmin at a dose level of 30 plasmin units (Loomis) per Kg.…”
Section: Histopathologic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control clots of the same age showed little decrease of radioactivity levels. A Resistance to lysis is apparent from the observation that most of the fibrinolytic effect is obtained within 24 hours after the first injection of plasmin, the remaining portions of the clot exhibiting less and less lysis during the subsequent days of treatment (2). It was found that the ability of plasmin at a dose level of 30 plasmin units (Loomis) per Kg.…”
Section: Histopathologic Findingsmentioning
confidence: 99%
“…Using this method, the in vivo fibrinolytic activity of human and bovine plasmin was demonstrated (2). Other proteolytic enzymes (crude pancreatic protease, trypsin, carboxypeptidase, papain and ficin) were ineffective in maximal tolerated doses (1,3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The time interval during which a clot remains susceptible to dissolution in a patient with thrombophlebitis is unknown. Studies on experimentally produced thrombi in the dog have indicated that success cannot be expected beyond the first 3 or 4 days.29' 38 Obviously, these results cannot be transferred directly to man. Experimentally formed clots in the dog may be handled quite differently in terms of organization and endothelialization than a spontaneously formed human clot.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recentlv, a new aspect has been added to From "fibrinolytic or thrombolytie agents," sinee they can induce the lysis of fibrin, the protein which provides the framework of intravascular thrombi. [28][29][30][31][32][33][34][35][36][37][38][39] Materials labeled as "fibrinolytic agents" Xvary widely in origin, composition, and mechaiiism of action.40 42 All of them, however, act by influencing or supplementing the normal components of the intrinsic fibrinolytic mechanism present in the blood ( fig. 1 43,44 These studies indicated that this preparation (a highly purified profibrinolysin activated with streptokiiiase and thenl further purified) was acceptable for use in humani subjects although it was niot devoid of side effects, particularly pyrogenicity.…”
mentioning
confidence: 99%